“Plan de negocio para la creación de una microempresa de comida rápida “Orlando’s Burgers” en el cantón La Maná, Provincia de Cotopaxi Año 2021”. - Ivonne Yomara, Almachi Cajas (2021)
This research entitled business plan for the creation of a fast-food microenterprise "Orlando's Burgers" in La Maná canton, Cotopaxi province, year 2021, was conducted in order to know the feasibility of the production and marketing of fast-food products. In order to fulfill the proposed purpose according to the objectives, it was necessary to carry out research: formative, bibliographic, descriptive and field research that allowed reaching theoretical and bibliographic information from various authors; likewise, the descriptive and field research was essential to diagnose the supply and demand of fast -food products through the application of the census directed to the owners and surveys directed to the consumers of the canton. Through the market study it was possible to establish that there was a demand of 198,840 and a supply of 168,000, giving an unsatisfied demand of 30,840 products, of which it was projected to cover with an annual production of 27,500 fast food products (hamburgers, papi pollo, hot dog, tostadas, salchipapa and burrito). The technical study also described the sketch of the location, availability of resources, production process, distribution of infrastructure, project requirements, organization and the legal framework necessary for the operation of the company. The economic and financial study showed that the total investment required was $11,942.00, 10% of which was financed through equity capital and the remaining 90% through a bank loan from Banecuador with an interest rate of 10.12%. A general equilibrium point of $0.82, the NPV for this fast food microenterprise "Orlando's Burgers" reflected a $ 41,313.70, an IRR of 109% and a cost-benefit ratio of $1.13, values that demonstrated the viability of this proposal.